(3GdGKfG YTQjI aj GdWgGQIs - (3GdMGQKj GdYGedj GdgePGfj, HgGA GdOjf, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g`s ((3JGL GdOjf eMeO Hf eQJVi QVj GdOjf MSjf Hf YHO GdUeO GdYGedjs)
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi BdGFg (B... (3Ef GdeWGdH GdeJYdbI HGdWgGQI GKfj YTQ WdHG ; GdChd eG GdWgGQI hGdKGfj ce GdWgGQI hGdKGdK deG GdWgGQI GdQGHY He GdWgGQI GdNGeS ee GdWgGQI GdSGOS Ydi eG GdWgGQI GdSGHY eJi GdWgGQI (B...s
(3BNQgG (B:s
.. (3aUd NGJeI (B: (3hJNJe gPg GdQSGdI HBOGH RjGQI GdCFeI Ydjge GdSdGe hJdc GdBOGH GKfj YTQ GdChd GdZSd bHd GdONhd (B...(3aEf Pdc QGLY dJYXje UGMH GdHbYI Ydjg GdSdGe (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6/102s
(3GdPQjYI (B1/82s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis